The impact of the housing crisis on self-reported health in Europe: multilevel longitudinal modelling of 27 EU countries - Clair, A; Stuckler, D; Loopstra, R; Reeves, A; Dorling, D; McKee, M (Oxford University Press, 2016)
Background: Many EU nations experienced a significant housing crisis during the Great Recession of 2008-2010. We evaluated the consequences of housing payment problems for people’s self-reported overall health. Methods: We used longitudinal data from the EU Statistics on Income and Living Conditions (EU-SILC) survey covering 27 countries from 2008-2010 to follow a baseline sample of persons who did not have housing debt and who were employed (45,457 persons, 136,371 person-years). Multivariate linear regression and multilevel models were used to evaluate the impact of transitions into housing arrears on self-reported health, correcting for the presence of chronic illness, health limitations, and other potential socio-demographic confounders. Results: Persons who transitioned into housing arrears experienced a significant deterioration in self-reported overall health by -0.03 units (95% CI -0.01 to -0.04), even after correcting for chronic illness, disposable income and employment status, and individual fixed effects. This association was independent and similar in magnitude to that for job loss (-0.02, 95% CI: -0.01 to -0.04). We also found that the impact of housing arrears was significantly worse among renters, corresponding to a mean 0.11 unit additional drop in health as compared with owner-occupiers. These adverse associations were only evident in persons below the 75th percentile of disposable income. Discussion: Our analysis demonstrates that persons who suffer housing arrears experience increased risk of worsening self-reported health, especially among those who rent. Future research is needed to understand the role of alternative housing support systems and available strategies for preventing the health consequences of housing insecurity.